Sequential acquisition of norfloxacin and ofloxacin resistance by methicillin-resistant and -susceptible Staphylococcus aureus. - Hori, S (1993)
The acquisition of ofloxacin resistance by a susceptible clinical Staphylococcus aureus strain was found to be achieved in two sequential steps: the first step was accompanied by 4-fold increases in the ofloxacin MIC and 8- to 16-fold increases in the norfloxacin MIC. The second step was accompanied by further increases in both the ofloxacin and the norfloxacin MICs. A mutation of the gyrA gene resulting in an amino acid substitution was found in the second-step but not in the first-step resistant subclone. On the other hand, there was no difference in the accumulation of norfloxacin in the parent strain and the resistant subclones of each step. The rates of mutation to resistance in the steps were (1.58 to 6.81) x 10(-9) and (0.71 to 2.59) x 10(-9), respectively, and did not depend on whether the parent strain was resistant to methicillin. Some implications of these observations for clinical as well as mechanistic aspects of the prevalence of methicillin- and ofloxacin-resistant S. aureus are discussed.